Impact of Firm Specific Factors on Financial Performance: A Comparative Study of Life and Non-Life Insurance Companies in Nepal - Jaishi, Bhupal; Poudel, Resam Lal (Prithvi Academic Journal, 2021)
The empirical research has been carried out to examine the firm specific factors composition and its impact on financial performance of life and non-life insurance companies in Nepal. This paper employs the descriptive as well as causal-comparative research design. The study comprises of a panel data set of 14 insurance companies listed in Nepal Stock Exchange (NEPSE) with 140 observations covering a period of 10 years from 2009/10 to 2018/19. The result exhibits that the insurance companies having a high debt ratio have better financial performance. It also reveals that a higher proportion of debt ratio and tangible assets increases return in assets. On the other side, a lesser proportion of equity, firm size and liquidity decreases the return on assets of the insurance companies in Nepal. The study raises understanding of impacts of firm specific factors on financial performance and provides an empirical evidence that the total debt ratio, equity to the total assets ratio, leverage, firm size, liquidity and tangibility are the significant factors in determining the financial performance of Nepal’s insurance companies. The non-life insurance companies tend to perform better in term of financial performance measured by earning per share and return on assets. The study leads to practical implications for insurance companies and regulatory bodies. The insurance companies of Nepal interested to improve their financial performance should focus on increasing their leverage and long-term investment and decreasing the proportion of equity, firm size and liquidity.